1752. Differential Degree and Duration of Cytomegalovirus (CMV) Viremia Between WHO International Standard-Calibrated Quantitative CMV Nucleic Acid Tests: Implications for Clinical Care - Meesing, Atibordee (Open Forum Infect Dis, 2019)
BACKGROUND: Quantitative nucleic acid amplification (QNAT) tests are cornerstone for the management of CMV disease after organ transplantation. We assessed the potential impact of viral load results obtained by two commercial WHO international standard-calibrated NAT in solid-organ (SOT) and hematopoietic stem cell transplant (HSCT) recipients. METHODS: Sixty-four patients (36 SOT and 28 HSCT) had plasma CMV viral load assessed using the COBAS AmpliPrep/COBAS TaqMan CMV Test (CAP/CTM; lower limit of quantification [LLoQ] at 137 IU/mL) and cobas 6800 System (cobas CMV; LLoQ at 35 IU/mL). Viral load values were correlated with clinical course and outcomes. RESULTS: Forty-three of 64 patients (67.2%) had CMV infection or disease (asymptomatic, 67.4%; gastrointestinal disease, 16.3%; pneumonitis 4.7%) at median of 4.4 months (IQR 1.4 to 7.7) from transplantation. At CMV infection diagnosis, viral load results (mean ± SD) were almost two-fold higher when measured by cobas CMV (19,456 ± 51,618 IU/mL) compared with CAP/CTM (10,504 ± 27,744 IU/mL; P = 0.04). Time to onset of CMV viremia was significantly shorter (11.5 days; P < 0.001) while viral clearance was significantly longer (12.75 days; P < 0.001) by cobas CMV when compared with CAP/CTM. Persistent viremia was observed with cobas CMV in 44% of patients at the time of first negative results by CAP/CTM. Patients with negative results by cobas CMV at the end of antiviral treatment had a significantly lower need for re-treatment (OR 0.26, 95% CI 0.04 to 0.99, P = 0.05). CONCLUSION: Our study highlights significant differences between CMV QNAT assays despite calibration to the WHO-international standard. The significant differences in the degree (almost two-fold), time to onset (12 days difference) and clearance (13 days difference) of CMV viremia between two automated commercial QNAT assays have direct implications in the care of transplant recipients. Persistence of low-level viremia was observed in samples that reached negative threshold by CAP/CTM, when tested using the more sensitive cobas CMV. Clearance of CMV viremia, when assessed by the more sensitive cobas CMV, was significantly associated with a lower need for re-treatment. DISCLOSURES: All authors: No reported disclosures.